The influence of variable slope‐water characteristics on dissolved oxygen levels in the northern California Current System. Issue 9 (21st September 2017) - Durski, Scott M.; Barth, John A.; McWilliams, James C.; Frenzel, Hartmut; Deutsch, Curtis
Abstract: Observations have suggested a trend of decreasing dissolved oxygen (DO) and increasing spiciness in summertime middepth slope waters and bottom shelf waters along the United States west coast over the past 50 years, but they have also demonstrated a large amount of interannual and decadal variability. Shelf bottom water and slope water properties can be influenced by both local and remote effects, including changes in circulation or changes in the characteristics of the source waters supplying the region. A regional‐scale, coupled physical biogeochemical model has been developed to simulate seasonal‐to‐decadal scale variability along the US west coast to discern the physical dynamics behind these spatial and temporal patterns. A simulation run from 1981 to 2006 with forcing that incorporates the larger scale interannual trends reproduces the development of low DO late in the upwelling season, the considerable interannual variability and the reported tendency toward a shoaling, more spicy, and oxygen‐depleted, northern California Undercurrent (CU). Whereas the trend in spiciness in the model results from increased influence of equatorial relative to subarctic source waters, the decreases in DO are found to additionally be a consequence of local biogeochemical processes. In order to better understand the interannual variability, years of the simulation were classified into four groups based on intensity of upwelling forcing and undercurrent strength. Slope water characteristics, shelf‐slope exchange, and slope‐basin exchange were compared across the four cases. Years with both strong upwelling and a strong undercurrent generated the most negative anomalies in slope‐water DO late in the upwelling season. Plain Language Summary: During the summertime, dissolved oxygen(DO) concentrations in coastal bottom waters sometimes decline to levels that stress a variety of the native organisms. These declines can be associated with local processes, such as enhanced respiration when the overlying waters are highly productive or remote influences such as the circulation of low DO water into these regions. The 'source waters', that are typically transported into the coastal region along the bottom, originate off the continental shelf, on the continental slope. Here we study the role of the slope water in altering the characteristics of the coastal bottom water by using a model simulation of both physical circulation and the principal biological processes. The model simulates the period 1981‐2006. We explore how trends in the characteristics of the slope water correlate with trends in the coastal waters and what physical phenomena are associated with the strongest DO declines in coastal bottom water. We find that years that have both high productivity due to upwelling of nutrient rich water onto the shelf and a strong northward flowing undercurrent along the continental slope tend to have the most negative impact. Key Points: Model results suggest that years with both strong upwelling and an intense California Undercurrent result in the lowest DO in slope bottom waters The long‐term trend toward declining shelf bottom water DO in the NCCS is associated with both large‐scale advection and local biogeochemical processes